Synthesis, Anticonvulsant and Antimicrobial Activities of Novel Mannich Bases of Isatin Derivatives - Vijey Aanandhi, M.; Vaidhyalingam, V.; George, Shiny (Asian Journal of Chemistry, 2010)
Some novel mannich base isatin derivatives were synthesized by reacting 1-(5-chloro-2-oxoindolin-3-ylidene)-4- (pyridine-2-yl)thiosemicarbazide with formaldehyde and several secondary amines. Their chemical structures were elucidated by means of spectral (FT-IR, 1H NMR and mass) analysis. Investigation of in vitro antibacterial and antifungal activity of synthesized compounds was done by disc diffusion method against B. subtilis, S. aureus, E. coli, P. aeruginosa, C. albicans and A. niger. All the synthesized compounds were screened for anticonvulsant activity by MES method using phenytoin as standard drug. All the compound exhibited moderate to good antibacterial and antifungal activity. All the compounds of the series exhibited significant anticonvulsant activity at 100 mg/kg dose level.